Polycarbonate Heat Molding for Soft Lithography. Issue 16 (29th March 2020) - Sonmez, Utku M.; Coyle, Stephen; Taylor, Rebecca E.; LeDuc, Philip R.
Abstract: Soft lithography enables rapid microfabrication of many types of microsystems by replica molding elastomers into master molds. However, master molds can be very costly, hard to fabricate, vulnerable to damage, and have limited casting life. Here, an approach for the multiplication of master molds into monolithic thermoplastic sheets for further soft lithographic fabrication is introduced. The technique is tested with master molds fabricated through photolithography, mechanical micromilling as well as 3D printing, and the results are demonstrated. Microstructures with submicron feature sizes and high aspect ratios are successfully copied. The copying fidelity of the technique is quantitatively characterized and the microfluidic devices fabricated through this technique are functionally tested. This approach is also used to combine different master molds with up to 19 unique geometries into a single monolithic copy mold in a single step displaying the effectiveness of the copying technique over a large footprint area to scale up the microfabrication. This microfabrication technique can be performed outside the cleanroom without using any sophisticated equipment, suggesting a simple way for high‐throughput rigid monolithic mold fabrication that can be used in analytical chemistry studies, biomedical research, and microelectromechanical systems. Abstract : The convenience of microfabrication by soft lithography is overshadowed by the challenges associated with master mold fabrication and maintenance. Here, a technique is introduced to clone master molds into monolithic thermoplastic sheets for further soft lithographic fabrication. This technique can be employed to copy a great variety of microfeatures at different scales ranging from the submicron level up to tens of centimeters.